Pengaruh Return On Assets (ROA) Dan Debt To Equity Ratio (DER) Terhadap Financial Distress : Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2022 - Endang Dwi Wahyuningsih; Aniqotunnafiah Aniqotunnafiah; Vira Nur Hidayah (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
The aim of this research is to determine the effect of Return on Assets (ROA) and Debt to Equity Ratio (DER) on Financial Distress in Manufacturing Companies in the Consumer Goods Industry Sector for the 2020-2022 period. The measure of Financial Distress used is the Altman Z-score. The method used in this research is descriptive research with a quantitative approach, using multiple linear regression analysis. The population of manufacturing companies in the Consumer Goods industry sector listed on the Indonesian Stock Exchange in 2020-2022 is 201 companies. The sampling technique used was purposive sampling technique, and a sample of 147 companies was obtained. The analysis used was Multiple Linear Regression with data processing tools in the form of SPSS v 19, The results of this research are that the Profitability Ratio proxied by Return on Assets (ROA) has a positive and significant effect on Financial Distress. Meanwhile, Leverage proxied by DER, according to the research results, has a negative and significant effect on Financial Distress.